The effects of sGnRHa implants on Piaractus mesopotamicus female breeders. An approach addressed to aquaculture - Kuradomi, Rafael Yutaka [UNESP]; Foresti, Fausto [UNESP]; Batlouni, Sergio Ricardo [UNESP] (Springer Nature, 2017)
In this study, we evaluated the potential use of sGnRHa slow-release implants (150 μg – Ovaplant®) for promoting an increased number of suitable Piaractus mesopotamicus females for induced spawning in a predictable period. To that, fshb, lhb, and gh gene expression, ovarian stereological evaluation and gonadal steroid concentrations were compared between treated and control females (n = 18) at 21, 35, and 115 days after sGnRHa implantation (DAI). The major differences between groups were observed at 35 DAI, when lhb and fshb were, respectively, up and downregulated for treated females compared to the controls, and the frequency of treated females in an advanced maturation class was higher (60%) than the controls (20%). Especially for promoting a significant change in the gonadotrophins gene expression levels, we demonstrated for the first time that sGnRHa slow-release implants has potential to be used to manipulate the reproductive cycle increasing the number of suitable Piaractus mesopotamicus females for induced spawning in a predictable period. However, a definitive protocol still depends on more studies involving a greater number of treatments and replicates.
Keywords: Implants; Ovarian maturation; Pacu; sGnRHa; Synchronization